The Political Economy of Brexit: Why Making It Easier to Leave the Club Could Improve the EU - Annette Bongardt; Francisco Torres (Intereconomics, 2016)
The UK exit from the EU represents a qualitative change in the nature of EU membership. On the one hand, it conveyed the lesson that for the Union to be sustainable, membership needs to entail constant caretaking as far as individual members' contributions to the common good are concerned, with both rights and obligations. Countries with preferences that are too divergent for the Union to function properly should then not be discouraged to invoke Article 50 and to opt instead for membership in the EEA or for a free trade agreement. The Union has to deliver to be sustainable, but it cannot do so if there is a constant hold up of decisions that are in the common interest. On the other hand, with the eurozone having established itself as the de facto core of European (political) integration, the UK's preference for a stand-alone (and incomplete) economic union became untenable, because the need to make the monetary union work calls for further integration and institution-building in the economic union sphere.
Keywords: 330; Referendum; EU-Mitgliedschaft; Wirkungsanalyse; Großbritannien; Eurozone